Potential Therapeutic Strategies for Intracranial Aneurysms Targeting Aneurysm Pathogenesis - Liu, Zhao; Ajimu, Kuerban; Yalikun, Naibijiang; Zheng, Yongtao; Xu, Feng (Frontiers in Neuroscience, 2019)
Subarachnoid hemorrhage resulting from intracranial aneurysms (IAs) is associated with high rates of morbidity and mortality. Although trigger mechanisms in the pathogenesis of IAs have not been fully elucidated, accumulating evidence has demonstrated that inflammation acts as a critical contributor to aneurysm pathogenesis. IAs is initiated by disruption and dysfunction of endothelial cells caused by abnormal wall shear stress. Subsequently, vascular inflammation can trigger a series of biochemical reactions resulting in vascular smooth muscle cells (VSMCs) apoptosis and migration, accompanied by inflammatory cell infiltration, secretion of various cytokines and inflammatory factors. These changes result in degradation of vascular wall, leading to the progression and eventual rupture of IAs. Increasing our knowledge of the pathogenesis of these lesions will offer physicians new options for prevention and treatment. In this study, we review aneurysmal pathogenesis to seek for safe, effective, and noninvasive therapeutic strategies.